(untitled) (Journal of the College of Education for Women, 2023)
The research problem is to determine the nature of the historical relationship between the profession of social work and volunteer work. Consequently, the research aims to investigate the nature of this relationship from a socio-historical perspective. Three axes have been used to analyze this relationship: the role of voluntary work in the development of the social work as a profession, the efforts made by social work to reach professionism and to distinguish it from voluntary work, and the relationship between social work and voluntary work. The research is qualitative analytical research and adopts the Mixed Methods Research (MMR). It identifies some literature for the analysis and implementation of a scoping process. It represents a systematic study approach to explore the socio-historical relationship between social work and voluntary work. To meet the objective of the study, the research sample has included several studies, research, and theoretical and scientific literature that address this historical relationship. The research has concluded the following: Voluntary work contributes to the emergence of the social work profession, as there is a strong relationship between them. Further, the formalization of the social work profession has an impact on the relationship with voluntary work, as government social workers would replace volunteers in providing many social services. As a result, the relationship between social work and volunteer work has evolved into a clear, strong, and solid collaboration. The research has recommended that the education curricula in Arab countries should imply the nature of the historical relationship of profession and voluntary work.